THE RAILWAYS AND THE WAR EFFORT, 1914-1915 - Bouch, R.J. (Scientia militaria : South African journal of military studies, 2012)
Political and administrative backgroundSubsequent to the creation of the Union of South Africa in 1910, steps were taken to combine the armed forces of the four excolonies in the new Union Defence Forces. Appropriate legislation was provided in the Defence Act of 1912. Considerable time was needed before all the provisos of the Act could be implemented, and the outbreak of war in August 1914 found the infant Defence Forces incomplete and unprepared for a task of the magnitude confronting them. One specific area where arrangements were inadequate was that of railway transport.